Men’s and Women’s Speech in Japanese - Szabó, László (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1991)
In Japanese there are several politeness levels, such as superpolite (honorific or humble), formal and informal. In polite and formal speech, women and men use more or less the same expressions. But in informal, abrupt speech, both men and women have their own style. This is the topic of this paper. There are men's and womens words, men's or women's particles, grammatical forms and constructions.